Relationship‐based care model in paediatrics: A randomized controlled trial to implement the parents’ perception of the quality of nursing care - De Barbieri, Ilaria; Sisti, Davide; Di Falco, Achille; Galeazzo, Marilena; Amatori, Stefano; Rocchi, Marco Bruno Luigi; Perilongo, Giorgio (Journal of advanced nursing, 2020)
Aim To evaluate whether the application of the Relationship‐based care model as a new treatment, called "Take 5 min", affects the level of anxiety, depression, and perceived quality of nursing care of parents of paediatric patients and the work satisfaction of the nursing staff. Design Single‐blind randomized controlled trial. Methods The trial was performed from February–July 2016. The trial was conducted with one intervention (N = 101) and one control group (N = 90). Nurses applied the treatment named “Take 5 Minutes”, which consisted of dedicating some short time (from 5 to 10 min) to the relationship with the parents using specifically designed communication strategies. The primary outcome was the evaluation of anxiety and depression of parents; the secondary was the parent perceived quality of nursing care. Results In the experimental group, participants had a lower level of anxiety and depression and highlighted that the effect of the “Take 5 Minutes” was proportional to the initial seriousness of parents’ anxiety and depression. Higher scores for the perception of the quality of care were given from the parents of the experimental group. Conclusion The “Take 5 Minutes” treatment offered to parents of paediatric patients demonstrated significant improvements in terms of their anxiety, depression, and perceived quality of nursing care. Impact Caregivers of paediatric patients are subject to psychological disorders such as depression and anxiety. The communication by the nursing community is of fundamental importance in the management of anxiety and depression in the caregivers of hospitalized patients. Caregivers who received the “Take 5 Minutes” treatment demonstrated a significant decrease in anxiety and depression compared with the control group caregivers. The perceived level of quality of nursing care showed a significant increase in the group of caregivers who received the T5M treatment. The RBC model does not require extra costs for health organizations and can be applied during the usual practice of care. Practices such as T5M could become part of paediatric patient care guidelines and nurses should be trained to apply them. Trial Registration Number Padua Research: ID No. 10,034; ClinicalTrials.gov: ID No. NCT04199429. 摘要 目的 评估关系型护理模式(又称“五分钟模式”)作为新的治疗方法是否会对患儿家长的焦虑、抑郁、护理感知质量及护理人员工作满意度等造成影响。 设计 单盲随机对照试验。 方法 试验时间为2016年2月至7月。试验过程中,设有一个干预组(N=101)和一个对照组(N=90)。护士采用名为“五分钟模式”的治疗方法,选择专门设计的交流策略,旨在花费短时间,缓和患儿与家长的关系(从5分钟到10分钟不等)。主要结果涉及家长焦虑抑郁的评定,其次是家长对护理质量的感知。 结果 实验组中,参与者的焦虑和抑郁水平较低,并且参与者强调“五分钟模式”治疗方法的效果与家长最初的焦虑和抑郁程度相关。实验组的家长对护理质量的认知得分更高。 结论 如果向患儿家长提供“五分钟模式”的治疗方法,其焦虑、抑郁和感知护理质量都将显著改善。 影响 患儿的照料者容易出现抑郁、焦虑等心理障碍。如果加强护理社区的沟通,护理人员的焦虑和抑郁情绪将得到控制。相较于对照组的护理者,接受“五分钟模式”治疗的护理者的焦虑和抑郁均显著降低。此外,接受“五分钟模式”治疗的护理者对护理质量的感知水平明显提高。如果选择RBC模式,则健康组织无需支付额外费用,并且通常情况下,这一模式可以在护理实践中应用。“五分钟模式”等实践可以用作患儿护理指南,并且,护士应该接受相关培训,以便确保可应用这些实践。 试验注册号 Padua Research:识别号10,034;ClinicalTrials.gov:识别号NCT04199429.